COMMUNITY SERVICE EDUCATES CADRES AND FAMILIES ABOUT SIMPLE TECHNIQUES OF MASSAGE ON THE UTERUS AFTER THE BABY IS BORN TO HELP THE UTERUS CONTRACT IN MEDAN TUNTUNGAN DISTRICT - Herlina; Deni Irawati; Khalyana Tantri (Cattleya Darmaya Fortuna, 2024)
The postpartum period is a critical phase that requires special attention, especially in preventing postpartum bleeding due to uterine atonia. This community service activity aims to increase the knowledge and practical skills of health cadres and families in performing simple massage techniques (massage) on the uterus after the baby is born to help uterine contractions. The activity was carried out in Medan Tuntungan District on April 26, 2024, involving the academic team from STIKes Darmo Medan as well as cadres and families as the main targets. The implementation method includes counseling and demonstration of direct uterine massage techniques. The success of the activity was evaluated through pre-test and post-test as well as observation of participants' practical abilities. The results of the activity showed an increase in participants' understanding and skills in taking independent actions as a first aid effort to prevent the risk of postpartum bleeding. Structured education on this technique is expected to create a family environment that is alert and independent in supporting postpartum maternal safety.